Composite fiber membrane as well as preparation method and application thereof

By using aqueous acetic acid solution and electrospinning technology, chitosan, polyethylene oxide and bioglass are mixed to prepare composite fiber membranes, which solves the problems of complex preparation, high cost and harmful solvents in the prior art, and achieves environmental protection and safety And excellent bone repair biofilm.

CN119392440APending Publication Date: 2025-02-07AMOCHEM MATERIAL SCI & TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411119867.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing composite fiber membrane preparation methods are complex, costly, and harmful organic solvents are often used, which have biological toxicity problems and are difficult to meet environmental protection and safety requirements.

Method used

Using aqueous acetic acid solution as solvent, chitosan, polyethylene oxide and bioglass are mixed, and composite fiber membranes are prepared through electrospinning technology to avoid the use of toxic organic solvents. The process is simple and the cost is low.

Benefits of technology

The prepared composite fiber membrane has good biocompatibility, degradability and mechanical properties, and is not biotoxic. It is suitable for bone repair biofilms that guide bone tissue regeneration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004996140790000061
    Figure BDA0004996140790000061
  • Figure BDA0004996140790000072
    Figure BDA0004996140790000072
  • Figure BDA0004996140790000081
    Figure BDA0004996140790000081
Patent Text Reader

Abstract

The invention discloses a composite fiber membrane as well as a preparation method and application thereof. The preparation method of the composite fiber membrane comprises the following steps: A, premixing deionized water and anhydrous acetic acid to form an acetic acid aqueous solution; b, taking one part of the acetic acid aqueous solution obtained in the step A, and adding chitosan into the acetic acid aqueous solution to obtain a first mixed solution; c, taking one part of the acetic acid aqueous solution obtained in the step A, and adding polyoxyethylene into the acetic acid aqueous solution to obtain a second mixed solution; d, mixing the first mixed solution and the second mixed solution, adding bioglass in the stirring process, and stirring until the bioglass is uniformly dispersed to obtain a spinning solution; and E, adding the spinning solution into electrostatic spinning equipment, and spinning to obtain the composite fiber membrane. The preparation process disclosed by the invention is relatively simple, relatively low in cost and environment-friendly, and the prepared composite fiber membrane has no biotoxicity and is suitable for being used as a bone repair biological membrane for guiding bone tissue regeneration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite fiber membrane and a preparation method and application thereof, in particular to a bone repair biological membrane suitable for guiding bone tissue regeneration and a preparation method thereof. Background Art

[0002] At present, bone injuries caused by diseases or accidents are relatively common, and conventional surgical treatments have limitations. Guided bone regeneration (GBR) is a very promising bone defect repair technology. The key is to cover the bone defect area with a layer of barrier membrane (GBR membrane) to prevent the surrounding connective tissue from growing into the bone defect area, providing a relatively closed growth space for bone tissue regeneration, thereby ensuring the normal progress of the bone regeneration process. The composite fiber membrane used as a barrier membrane needs to meet the requirements of good biocompatibility, biodegradability, and non-toxicity.

[0003] For example, patent CN113117150A discloses a guided tissue regeneration membrane, which includes a fiber aggregate and a shaping body; the fiber aggregate is interwoven by first fibers, and the shaping body contains at least one second fiber, the first fiber and the second fiber are interlaced with each other, and a part of the first fiber is adhered to the surface of the second fiber; wherein the diameter of the second fiber is greater than the diameter of the first fiber. This guided tissue regeneration membrane has high mechanical strength and meets the requirements of degradability and biocompatibility. However, the preparation process is relatively complicated, and it requires electrospinning technology combined with 3D printing technology, the equipment cost is high, and the overall manufacturing cost is extremely high.

[0004] There are also some methods for preparing guided tissue regeneration membranes that directly use electrospinning technology, but most of them require the use of harmful organic solvents, which are not environmentally friendly and may have biological toxicity.

[0005] The above information disclosed in the Background section is only for enhancement of understanding of the background of the present application and therefore it may contain information that does not constitute the prior art that is already known to a person of ordinary skill in the art. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a composite fiber membrane, which has a relatively simple process, low cost, and is environmentally friendly. The prepared composite fiber membrane has no biological toxicity and is suitable for use as a bone repair biomembrane for guiding bone tissue regeneration.

[0007] To achieve the above object, the present invention adopts the following technical solutions.

[0008] A method for preparing a composite fiber membrane comprises the following steps:

[0009] A. premixing deionized water and anhydrous acetic acid to form an acetic acid aqueous solution;

[0010] B. Take a portion of the acetic acid aqueous solution obtained in step A, and add chitosan thereto to obtain a first mixed solution;

[0011] C. Take a portion of the acetic acid aqueous solution obtained in step A, add polyethylene oxide thereto, and obtain a second mixed solution;

[0012] D. mixing the first mixed solution and the second mixed solution, adding bioglass during stirring, and stirring until the mixture is evenly dispersed to obtain a spinning solution;

[0013] E. Adding the spinning solution into an electrospinning device to spin to obtain the composite fiber membrane.

[0014] Preferably, in step A, the weight ratio of anhydrous acetic acid to deionized water is (2-5):(3-8).

[0015] More preferably, in step B, 3 to 7 parts by weight, preferably 4 to 7 parts by weight, of chitosan and 40 to 50 parts by weight of aqueous acetic acid are taken.

[0016] More preferably, in step C, 3 to 7 parts by weight, preferably 3 to 6 parts by weight, of polyethylene oxide and 40 to 50 parts by weight of aqueous acetic acid are used.

[0017] In some embodiments, the concentration and / or amount of the acetic acid aqueous solution taken in step B is the same as or different from that of the acetic acid aqueous solution taken in step C.

[0018] Preferably, in step D, 8 to 12 parts by weight of bioglass are added.

[0019] Preferably, in step D, after the bioglass is evenly dispersed, it is shaken in an ultrasonic water bath at 60° C. for 0.5 to 2 hours to obtain the spinning solution.

[0020] Preferably, in step E, spinning is performed for 3 hours at a receiving distance of 20 cm and a voltage of 30 kV to obtain the composite fiber membrane.

[0021] Preferably, in step A, deionized water and anhydrous acetic acid are mixed by magnetic stirring; in step B, chitosan and acetic acid aqueous solution are mixed uniformly by magnetic stirring; in step C, polyethylene oxide and acetic acid aqueous solution are mixed uniformly by magnetic stirring.

[0022] A composite fiber membrane, the raw materials of which include: 4-7 weight parts of chitosan, 3-6 weight parts of polyethylene oxide, 8-12 weight parts of bioglass, 30-80 weight parts of acetic acid and 20-50 weight parts of deionized water.

[0023] Preferably, the composite fiber membrane is prepared by the preparation method described above.

[0024] A composite fiber membrane prepared by the preparation method or use of the composite fiber membrane in preparing bone repair products.

[0025] Due to the application of the above technical solution, the present invention has the following advantages:

[0026] The composite fiber membrane of the present invention uses chitosan, polyethylene oxide and bioglass as main raw materials, and adopts acetic acid and deionized water to mix and disperse the above main raw materials to obtain a spinning solution. The spinning solution has good spinnability and can be used to prepare membrane materials by electrostatic spinning. The process is simple and avoids the use of toxic organic solvents, which is environmentally friendly. The prepared composite fiber membrane has no biological toxicity, has excellent mechanical properties, and has good hydrophilicity and wettability, which is conducive to cell attachment. It is suitable for use as a bone repair biomembrane for guiding bone tissue regeneration. DETAILED DESCRIPTION

[0027] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0028] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.

[0029] In this paper, electrospinning technology is used to prepare a composite fiber membrane loaded with bioglass, which can be placed between soft tissue and bone defects to achieve bone tissue repair and regeneration. On the one hand, it can provide growth space for the bone tissue under the membrane and promote bone tissue regeneration, and on the other hand, it can shield the infiltration of non-osteoblasts.

[0030] Chitosan (CS) is a material obtained by removing some acetyl groups from natural polysaccharides. It is biodegradable, non-toxic, and has good biocompatibility and antibacterial properties. However, chitosan has poor mechanical properties and spinnability, which limits its application as a biofilm. In most cases, chitosan solutions are difficult to electrospin due to the lack of chain entanglement and high surface tension. Polyethylene oxide (PEO) can reduce viscosity through hydrogen bonds, is non-toxic and can form a gel, and adding it to the system can improve spinnability. Bioglass is glass that can achieve specific biological and physiological functions. When bioglass is implanted into the bone defect site of the human body, it can directly combine with bone tissue to repair bone tissue and restore its function. The present invention uses bioactive glass (phytic acid derived bioactive CaO-P2O5-SiO2 gel-glasses, PSC) synthesized with phytic acid as a precursor.

[0031] Description of raw materials used:

[0032] Chitosan (CS): CAS No. 9012-76-4, deacetylation degree ≥ 95%, viscosity 100-200mpa.s, purchased from Aladdin Polyethylene oxide (PEO): CAS No. 68441-17-8, average Mv ~ 600,000, purchased from Aladdin

[0033] Bioglass: Bioactive glass synthesized with phytic acid as a precursor (phytic acid derived bioactive CaO-P2O5-SiO2 gel-glasses, PSC)

[0034] Anhydrous acetic acid: CAS No. 64-19-7, purchased from Jincheng Reagent

[0035] Example 1

[0036] 1. Premix 20 parts of deionized water with 20 parts of anhydrous acetic acid, rotate at 500 rpm, and stir magnetically for 30 minutes.

[0037] 2. Pour the mixed acetic acid aqueous solution into a three-necked round-bottom flask, weigh 5 parts of chitosan and add it, and stir it magnetically for 24 hours. A condenser is connected to the middle of the three-necked round-bottom flask. This device is suitable for long-term stirring and can minimize the evaporation of acetic acid.

[0038] 3. Premix 20 parts of deionized water with 20 parts of anhydrous acetic acid, rotate at 500 rpm, and stir magnetically for 30 minutes.

[0039] 4. Pour the above acetic acid aqueous solution into a beaker, weigh 5 parts of polyethylene oxide, pour it into a three-necked flask, and stir magnetically for 24 hours.

[0040] 5. Mix the chitosan solution and polyethylene oxide solution mentioned above, add 10 parts of bioglass during stirring, and stir for 1 hour until they are evenly dispersed.

[0041] 6. Place in an ultrasonic water bath at 60°C and shake for 1 hour to complete the mixing of the spinning solution.

[0042] 7. Add the spinning solution into the syringe and spin for 3 hours at a receiving distance of 20 cm and a voltage of 30 kV to obtain a chitosan-polyethylene oxide-bioglass spinning membrane.

[0043] Example 2

[0044] 1. Premix 15 parts of deionized water with 35 parts of anhydrous acetic acid, rotate at 500 rpm, and stir magnetically for 30 minutes.

[0045] 2. Pour the mixed acetic acid aqueous solution into a three-necked round-bottom flask, weigh 6 parts of chitosan and add it, connect a condenser to the middle flask, and stir magnetically for 24 hours.

[0046] 3. Premix 15 parts of deionized water with 35 parts of anhydrous acetic acid, rotate at 500 rpm, and stir magnetically for 30 minutes.

[0047] 4. Pour the above acetic acid aqueous solution into a beaker, weigh 4 parts of polyethylene oxide, pour into a three-necked flask, and stir magnetically for 24 hours.

[0048] 5. Mix the chitosan solution and polyethylene oxide solution mentioned above, add 10 parts of bioglass during stirring, and stir for 1 hour until they are evenly dispersed.

[0049] 6. Place in an ultrasonic water bath at 60°C and shake for 1 hour to complete the mixing of the spinning solution.

[0050] 7. Add the spinning solution into the syringe and spin for 3 hours at a receiving distance of 20 cm and a voltage of 30 kV to obtain a chitosan-polyethylene oxide-bioglass spinning membrane.

[0051] Example 3

[0052] 1. Premix 10 parts of deionized water with 40 parts of anhydrous acetic acid, rotate at 500 rpm, and stir magnetically for 30 minutes.

[0053] 2. Pour the mixed acetic acid aqueous solution into a three-necked round-bottom flask, weigh 7 parts of chitosan and add it, connect a condenser to the middle flask, and stir magnetically for 24 hours.

[0054] 3. Premix 10 parts of deionized water with 40 parts of anhydrous acetic acid, rotate at 500 rpm, and stir magnetically for 30 minutes.

[0055] 4. Pour the above acetic acid aqueous solution into a beaker, weigh 3 parts of polyethylene oxide, pour into a three-necked flask, and stir magnetically for 24 hours.

[0056] 5. Mix the chitosan solution and polyethylene oxide solution mentioned above, add 10 parts of bioglass during stirring, and stir for 1 hour until they are evenly dispersed.

[0057] 6. Place in an ultrasonic water bath at 60°C and shake for 1 hour to complete the mixing of the spinning solution.

[0058] 7. Add the spinning solution into the syringe and spin for 3 hours at a receiving distance of 20 cm and a voltage of 30 kV to obtain a chitosan-polyethylene oxide-bioglass spinning membrane.

[0059] Example 4

[0060] 1. Premix 25 parts of deionized water with 15 parts of anhydrous acetic acid, rotate at 500 rpm, and stir magnetically for 30 minutes.

[0061] 2. Pour the mixed acetic acid aqueous solution into a three-necked round-bottom flask, weigh 4 parts of chitosan and add it, connect a condenser to the middle flask, and stir magnetically for 24 hours.

[0062] 3. Premix 25 parts of deionized water with 15 parts of anhydrous acetic acid, rotate at 500 rpm, and stir magnetically for 30 minutes.

[0063] 4. Pour the above acetic acid aqueous solution into a beaker, weigh 6 parts of polyethylene oxide, pour into a three-necked flask, and stir magnetically for 24 hours.

[0064] 5. Mix the chitosan solution and polyethylene oxide solution mentioned above, add 10 parts of bioglass during stirring, and stir for 1 hour until they are evenly dispersed.

[0065] 6. Place in an ultrasonic water bath at 60°C and shake for 1 hour to complete the mixing of the spinning solution.

[0066] 7. Add the spinning solution into the syringe and spin for 3 hours at a receiving distance of 20 cm and a voltage of 30 kV to obtain a chitosan-polyethylene oxide-bioglass spinning membrane.

[0067] Comparative Example 1

[0068] 1. Premix 35 parts of deionized water and 35 parts of anhydrous acetic acid at a speed of 500 rpm and stir magnetically for 30 minutes.

[0069] 2. Pour the mixed acetic acid aqueous solution into a three-necked round-bottom flask, weigh 10 parts of chitosan and add it, connect a condenser to the middle flask, and stir magnetically for 24 hours.

[0070] 3. Add 20 parts of bioglass under stirring and stir for 1 hour until evenly dispersed.

[0071] 4. Place in an ultrasonic water bath at 60°C and shake for 1 hour to complete the mixing of the spinning solution.

[0072] 5. Add the spinning solution into the syringe and spin for 3 hours at a receiving distance of 20 cm and a voltage of 30 kV to obtain a chitosan-polyethylene oxide-bioglass spinning membrane.

[0073] Comparative Example 2

[0074] 1. Premix 37.5 parts of deionized water and 37.5 parts of anhydrous acetic acid at a speed of 500 rpm and stir magnetically for 30 minutes.

[0075] 2. Pour the above acetic acid aqueous solution into a beaker, weigh 5 parts of polyethylene oxide, pour it into a three-necked flask, and stir magnetically for 24 hours.

[0076] 3. Mix the chitosan solution and polyethylene oxide solution, add 20 parts of bioglass during stirring, and stir for 1 hour until they are evenly dispersed.

[0077] 4. Place in an ultrasonic water bath at 60°C and shake for 1 hour to complete the mixing of the spinning solution.

[0078] 5. Add the spinning solution into the syringe and spin for 3 hours at a receiving distance of 20 cm and a voltage of 30 kV to obtain a chitosan-polyethylene oxide-bioglass spinning membrane.

[0079] The specific formulas of the above embodiments and comparative examples are shown in Table 1 below.

[0080] Table 1

[0081]

[0082]

[0083] Among them, the weight proportion of bioglass in Comparative Examples 1 and 2 is 20. If it is less than 20, for example, 10 parts, the spinnability of the obtained spinning solution is poor, the spinning effect is poor, and it is difficult to obtain a fiber membrane that meets the test requirements.

[0084] In Examples 1 to 4 and Comparative Examples 1 to 2, the parts of raw materials are all parts by weight; the spinning parameters are all: the distance from the needle to the receiving surface is 20 cm, the voltage is 30 kV, the spinning is 3 hours, and the spinning film is collected.

[0085] Performance Testing

[0086] 1. Spinning state and membrane appearance

[0087] The state of the spinning layer was visually observed and recorded. The results are shown in Table 2 below.

[0088] Table 2

[0089]

[0090] Conclusion: The spinning effects of Examples 1 and 4 are relatively good, and Example 1 has a better surface appearance. In order to achieve the best spinning effect, the weight of chitosan is controlled between 3 and 7, and the weight of polyethylene oxide is controlled between 3 and 7.

[0091] 2. Film tensile test

[0092] The membranes of Examples 1 to 4 and Comparative Examples 1 and 2 were cut into a size of 10*1.5 cm and subjected to a tensile property test on a tensile testing machine in accordance with GB / T1040-2006. The test results are shown in Table 3 below.

[0093] Table 3

[0094]

[0095] Conclusion: The film layers of Examples 1 and 4 have better mechanical properties

[0096] 3. Surface wettability test

[0097] The surface wettability of the membranes of Examples 1 to 4 and Comparative Examples 1 and 2 was tested using a Rame-Hart 250 standard contact angle tester. A 2 cm × 5 cm chitosan-polyethylene oxide-bioglass membrane was bonded to a movable sample stage. Subsequently, 4 μl of distilled water was dropped on several different locations on the membrane surface using a microsyringe. The contact angles on both sides of the water drop were measured to ensure symmetry and horizontality. The test results are shown in Table 4 below.

[0098] Table 4

[0099] Serial number Contact angle (θ) Example 1 39.10 Example 2 35.35 Example 3 34.15 Example 4 45.30 Comparative Example 1 Can't test it, the water droplets just flattened it Comparative Example 2 Can't test it, the water droplets just flattened it

[0100] When the contact angle is less than 90 degrees, the surface of the film is called hydrophilic, indicating that the liquid easily wets the film and spreads on it. Good hydrophilicity and wettability are conducive to the attachment of cells between biofilm materials and promote cell proliferation. The chitosan-polyethylene oxide-bioglass film layers of Examples 1 to 4 all have good wettability. The contact angle should be in the range of 30-60 for the best.

[0101] 4. Alkaline phosphatase activity (ALP)

[0102] The osteogenic effect of cells on different membrane layers of Examples 1 to 4 and Comparative Examples 1 and 2 was determined by evaluating the alkaline phosphatase (ALP) activity at 0, 7, 14, and 21 days. The biofilm was washed with PBS, and then the chitosan-polyethylene oxide-bioglass membrane layers were placed at the bottom of the culture plate, ALP (purchased from Sigma) was added, and incubated for 1 hour. After the addition of ALP, it catalyzed the hydrolysis of the colorless organic phosphate substrate p-nitrophenyl phosphate to p-nitrophenol to form a yellow product. Subsequently, 2NNaOH was added to stop the reaction. The absorbance was then read at 405nm using a Victor X3 microplate reader. See Table 5 below for the test results.

[0103] Table 5

[0104]

[0105] Due to the limited surface area of ​​the cell culture dish, once the cells reach fusion at a certain time, the proliferation rate will decrease, leading to cell death. Therefore, too high a concentration of bioglass cannot positively promote the proliferation of osteoblasts, but will lead to cell death at 21 days. The weight ratio of bioglass in the total raw materials is preferably controlled between 1% and 15%.

[0106] In summary, the preparation process of the composite fiber membrane in the above embodiment is simple and suitable for mass production; while ensuring that the composite fiber membrane meets the requirements of biocompatibility, degradability and non-toxicity, it avoids the use of harmful organic solvents and also has good mechanical properties, and the spinning solution has good spinnability.

[0107] As shown in this specification and claims, the terms "comprises" and "include" only indicate the inclusion of the steps and elements that have been clearly identified, and these steps and elements do not constitute an exclusive list, and the method or device may also include other steps or elements. The term "and / or" as used herein includes any combination of one or more of the relevant listed items.

[0108] The above embodiment is only for illustrating the technical concept and features of the present invention, and is a preferred embodiment. Its purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and it cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the principle of the present invention should be included in the protection scope of the present invention.

[0109] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A method for preparing a composite fiber membrane, characterized in that: The steps include: A. premixing deionized water and anhydrous acetic acid to form an acetic acid aqueous solution; B. Take a portion of the acetic acid aqueous solution obtained in step A, and add chitosan thereto to obtain a first mixed solution; C. Take a portion of the acetic acid aqueous solution obtained in step A, add polyethylene oxide thereto, and obtain a second mixed solution; D. mixing the first mixed solution and the second mixed solution, adding bioglass during stirring, and stirring until the mixture is evenly dispersed to obtain a spinning solution; E. Adding the spinning solution into an electrospinning device to spin to obtain the composite fiber membrane.

2. The preparation method according to claim 1, characterized in that: In step A, the weight ratio of anhydrous acetic acid to deionized water is (2-5):(3-8).

3. The preparation method according to claim 2, characterized in that: In step B, 3-7 parts by weight of chitosan and 40-50 parts by weight of acetic acid aqueous solution are taken.

4. The preparation method according to claim 2, characterized in that: In step C, 3 to 7 parts by weight of polyethylene oxide and 40 to 50 parts by weight of acetic acid aqueous solution are taken.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step D, 8 to 12 parts by weight of bioglass are added.

6. The preparation method according to any one of claims 1 to 4, characterized in that: In step D, after the bioglass is evenly dispersed, it is shaken in an ultrasonic water bath at 60° C. for 0.5 to 2 hours to obtain the spinning solution.

7. The preparation method according to any one of claims 1 to 4, characterized in that: In step E, spinning is performed for 3 hours at a receiving distance of 20 cm and a voltage of 30 kV to obtain the composite fiber membrane.

8. The preparation method according to any one of claims 1 to 4, characterized in that: In step A, deionized water and anhydrous acetic acid are mixed by magnetic stirring; in step B, chitosan and acetic acid aqueous solution are mixed uniformly by magnetic stirring; in step C, polyethylene oxide and acetic acid aqueous solution are mixed uniformly by magnetic stirring.

9. A composite fiber membrane, characterized in that: Ingredients include: 3-7 parts by weight of chitosan, 3-7 parts by weight of polyethylene oxide, 8-12 parts by weight of bioglass, 30-80 parts by weight of acetic acid and 20-50 parts by weight of deionized water.

10. The composite fiber membrane according to claim 9, characterized in that: The composite fiber membrane is prepared by the preparation method according to any one of claims 1 to 8.

11. Use of the composite fiber membrane prepared by the preparation method according to any one of claims 1 to 8 or the composite fiber membrane according to claim 8 in the preparation of bone repair products.

Citation Information

Patent Citations

  • Guided tissue regeneration membrane as well as preparation method and application thereof

    CN113117150A

  • Method for preparing chitosan-based superfine fiber carrier material for medical dressing

    CN103394114A

  • Method for preparing regenerated cellulose composite bioglass tissue repair material

    CN107213519A

  • Preparation method of chitosan / polyoxyethylene composite fiber membrane

    CN116555980A

  • Nanometer ultrafine fibre film material of chitose and its preparation method

    CN1569254A